2021
DOI: 10.3390/agronomy11040739
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Hemin Confers Cadmium Tolerance by Decreasing Cadmium Accumulation and Modulating Water Status and Matter Accumulation in Maize Seedlings

Abstract: Cadmium (Cd) contamination harms plant growth and human health. The application of hemin (ferroprotoporphyrin IX) can effectively relieve abiotic stresses in plants. This work investigates the effects of hemin on alleviating Cd toxicity and enhancing Cd tolerance in maize seedlings. In this study, maize seedlings were cultivated in nutrient solutions, with a combination of CdCl2 (464 μmol L−1) and hemin (100 μmol L−1). We measured plant growth status, water status, Cd concentration, and Cd distribution in maiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…As a result, leaf relative water content (LRWC) is a reliable indicator of a plant’s ability to handle stress. In the present study, the LRWC in E. sativa seedlings under Cd-stress was significant decreased in comparison with the controlled seedlings [ 34 ].…”
Section: Discussionmentioning
confidence: 77%
“…As a result, leaf relative water content (LRWC) is a reliable indicator of a plant’s ability to handle stress. In the present study, the LRWC in E. sativa seedlings under Cd-stress was significant decreased in comparison with the controlled seedlings [ 34 ].…”
Section: Discussionmentioning
confidence: 77%
“…Foliar application of Hemin positively regulated various morphological indicators and promoted shoot growth and biomass accumulation in rice seedlings. Liu et al (2021) showed that Hemin improved the growth of maize seedlings and increased biomass accumulation under drought stress. Furthermore, Hemin was degraded in plants to produce CO, which alleviated the inhibition of wheat growth by NaCl stress ( Ling et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Reference [ 39 ] pointed out that the root system has flexibility and plasticity and can adjust its shape in time to reduce the absorption of toxic ions. After hemin treatment, the root–shoot ratio of seedlings increased significantly ( Table S3 ), possibly because hemin promoted the growth and development of plants by promoting root growth to absorb more water and nutrients and ensure the normal growth of plants under stress [ 40 ]. In addition, the increase in root-to-shoot ratio can also increase the carbon fixation capacity of plants and promote photosynthesis and biomass accumulation [ 41 ].…”
Section: Discussionmentioning
confidence: 99%